#41: Examining the Role of Rurality on the Incidence of Acute Respiratory Illnesses, Overall Antibiotic Use and Inappropriate Antibiotic Use Among Young Children in Tennessee. (26th March 2021) - Dantuluri, K; Bruce, J; Edwards, K; Howard, L; Grijalva, C
Abstract: Background: The Centers for Disease Control and Prevention (CDC) defines inappropriate antibiotic use as prescribing antibiotics not in accordance with national and local evidence-based guidelines, wrong selection of antibiotics, wrong dosing of antibiotics, or wrong duration of antibiotic use. Inappropriate antibiotic use has been associated with the development and transmission of antibiotic-resistant organisms. Acute respiratory illnesses (ARI) are the leading causes of antibiotic use among children with rates of antibiotic use in Tennessee children among the highest in the United States. The reasons for this have not been adequately assessed, particularly in children enrolled in the Tennessee Medicaid (TennCare) program, who tend to live in low-income households and rural locales and are disproportionately underrepresented in database studies conducted in large managed care organizations. We sought to examine whether the rates of ARI-related overall antibiotic use and inappropriate antibiotic use among young children enrolled in TennCare vary by the rurality of their county of residence. Methods: This was a retrospective cohort study of children aged 2 months–5 years enrolled in TennCare from July 1, 2007, to June 30, 2017. We used pharmacy and healthcare claims data to calculate the incidence of ARI and ARI-related antibiotic use. Each eligible child entered into the cohort at the earliest time when selection criteria were met, and follow-up continued from cohort entry until the earliest of loss of enrollment, death, end of study, or meeting exclusion criteria. ARI was identified using International Classification of Diseases, Ninth and Tenth Revisions (ICD-9 and ICD-10) and ARI-related antibiotic use was defined as an antibiotic prescription filled within 72 hours of an ARI. ARI-related antibiotic use was classified as potentially appropriate or inappropriate using a previously published CDC classification system. The rurality of children's county of residence was defined as either mostly urban, mostly rural, or completely rural based upon the United States Census Bureau definitions. We calculated incidence rates for ARI, ARI-related antibiotic use, and ARI-related inappropriate antibiotic use. To assess the effect of rurality of residence on these outcomes, we used multivariable mixed-effects Poisson regression. These analyses accounted for other factors including child age, gender, race, underlying comorbidities, calendar year and month, and history of antibiotic exposure. Results: In total, 813, 432 children met enrollment criteria and contributed a total of 2, 057, 272 person-years for the cohort. Overall, the rate of ARIs, antibiotic use associated with ARIs, and inappropriate antibiotic use associated with ARIs has trended down over time (Figure 1A). There were higher rates of these three outcomes in children who live in mostly rural and completely rural counties compared with those who live in mostly urban counties (Figure 1B–D). Conclusions: Children who live in rural counties in Tennessee are disproportionately affected by higher rates of ARIs, antibiotic use, and inappropriate antibiotic use compared with those who live in urban counties. These findings can inform targeted stewardship interventions to reduce inappropriate antibiotic prescribing and to decrease the rates of antibiotic-resistant infections.